Kesempatan Investasi Dan Determinan Kebijakan Pendanaan Perusaahaan Publik Indonesia - Pasaribu, Rowland Bismark Fernando; Kowanda, Dionysia (UNIVERSITAS NEGERI SURABAYA, 2013)
AbstractThis research aimed to test whether there are differences among companies which have the growth potential and barren of in the case of policy of financing and also to test significance influence of unsystematic risk, size, profitability, and liquidity to non-financial companies financing structure enlisted in Indonesian Stock exchange Period 2008-2011. The result of this research indicate that except of debt equity ratio, size, and unsystematic risk, generally, there is differences of all proxy (leverage, profitability, and liquidity) between company which have the potency to grow and barren of. Hitting the influence significantly, in simultaneously all proxy used have a significant influence to structure of company financing in both classification refer to IOS.